Na przekór okupacyjnej rzeczywistości. Warszawski humor w "Cafe pod Minogą" Bronisława Broka = Despite Nazi occupation. Warsaw humour in "Cafe pod Minogą" ("Oct opus Café") directed by Bronisław Brok - Trojanowski, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The 1959 film "Cafe pod Minogą" ("Octopus Cafe"), directed by Bronisław Brok and based on a novel by Stefan Wiechecki, belongs to very few Polish comedies that show Warsaw under the occupation, asseen by the residents. The protagonists, supporting one another in the face of the tragedy and defiantagainst enslavement, neutralise the atrocities of war with humour and optimistic faith in a betterfuture. Despite its local character, the sense of humour of the residents of Warsaw is of universal value.
Keywords: Wiechecki, Stefan (1896-1979); Brok, Bronisław (1906-1975); adaptacja filmowa